The search for security in precarious times: non-traditional graduates perspectives on higher education and employment - Finnegan, Fergal (2021)
This article explores non-traditional student and graduate views of the university in Ireland and Portugal as it relates to their expectations of, and experiences in, the labour market. The research is based on in-depth biographical interviews with 61 non-traditional students and graduates conducted longitudinally (85 interviews in total). The article contextualises the research in relation to the expansion of higher education internationally as well as national and EU policies aimed at supporting a ‘knowledge-based economy’. It offers an overview of the meaning of precarity. It then outlines key empirical findings from the research related to student expectations of their degree and their postgraduation experience in the labour market. In particular, it explores the phenomenon of precarity amongst graduates how this is experienced and handled in various ways. Using a critical and egalitarian lens the overall aim of the research is to widen the focus of widening participation debates and explore how educational and institutional initiatives impact, or not, on wider social and employment inequalities.